Phylogenetic Relatedness and Genome Structure of Yersinia ruckeri Revealed by Whole Genome Sequencing and a Comparative Analysis - Abdel-Glil, Mostafa Y.; Fischer, Uwe; Steinhagen, Dieter; McCarthy, Una; Neubauer, Heinrich; Sprague, Lisa D. (Frontiers in Microbiology, 2021)
Yersinia ruckeri is the causative agent of enteric redmouth disease (ERM), a serious infection that affects global aquaculture with high economic impact. The present study used whole genome sequences to perform a comparative analysis on 10 Y. ruckeri strains and to explore their genetic relatedness to other members of the genus. Y. ruckeri, Y. entomophaga and Y. nurmii formed a species complex that constitutes the most basal lineage of the genus. The results showed that the taxonomy of Y. ruckeri strains is better defined by using a core genome alignment and phylogenetic analysis. The distribution of accessory genes in all Yersinia species revealed the presence of 303 distinctive genes in Y. ruckeri. Of these, 169 genes were distributed in 17 genomic islands potentially involved in the pathogenesis of ERM via (1) encoding virulence factors such as Afp18, Yrp1, phage proteins and (2) improving the metabolic capabilities by enhancing utilisation and metabolism of iron, amino acids (specifically, arginine and histidine), and carbohydrates. The genome of Y. ruckeri is highly conserved regarding gene structure, gene layout and functional categorisation of genes. It contains various components of mobile genetic elements but lacks the CRISPR-Cas system and possesses a stable set of virulence genes possibly playing a critical role in pathogenicity. Distinct virulence plasmids were exclusively restricted to a specific clonal group of Y. ruckeri (CG4), possibly indicating a selective advantage. Phylogenetic analysis of Y. ruckeri genomes revealed the co-presence of multiple genetically distant lineages of Y. ruckeri strains circulating in Germany. Our results also suggest a possible dissemination of a specific group of strains in the USA, Peru, Germany and Denmark. In conclusion, this study provides new insights into the taxonomy and evolution of Y. ruckeri and contributes to a better understanding of the pathogenicity of ERM in aquaculture. The genomic analysis presented here offers a framework for the development of more efficient control strategies for this pathogen.